MULTISENSORY APPROACH IN TEACHING STUDENTS WITH READING CHALLENGES - Espino, John Paul (International Journal of Arts, Sciences and Education, 2025)
This research, "Multisensory Approach in Teaching Students with Reading Challenges”, investigates the effectiveness of the multisensory approach in enhancing reading abilities among Grade 9 students of Isulan National High School. A quasi-experimental design was applied to 79 participants, with two experimental cohorts. The Phil-IRI 2018 Manual measured word recognition and reading comprehension levels prior to and after intervention. Findings showed a significant positive impact of the multisensory approach on reading performance, with students in the frustration level decreasing and students at the instructional and independent levels increasing. Research underscored areas focusing on the effectiveness of visual, auditory, and kinesthetic methods and other multisensory learning activities to complement students’ reading skills and recommends further study of the extended long-term effect of the multisensory method. The study posits that the implementation of visual, auditory, and kinesthetic strategies can effectively support students’ reading abilities, extrapolating the multisensory strategy to end the literacy crisis in the Philippines.